Experiments in Decolonizing the University Towards an Ecology of Study - Schildermans, Hans (Radical Politics and Education, 2021)
The book addresses the need to reconsider the relation between university and society, a debate that has been going on from the Middle Ages to Kant, Humboldt, Newman, and beyond. Hans Schildermans builds on the philosophy and theory of higher education, drawing on the work of John Dewey, Donna Haraway, William James, Bruno Latour, Martin Savransky, Isabelle Stengers and Alfred North Whitehead. In relation to the study practices of the Palestinian experimental university 'Campus in Camps', he develops the concept of an ecology of study to approach the relation between university and society from a new angle. The book avoids the two positions that are traditionally defended, namely the idea of the autonomous university where research and teaching are performed 'in freedom and solitude' on the one hand, and the capitalized university that produces useful knowledge on the other hand. Schildermans emphasizes the importance of study practices as a site of resistance against current neoliberal and capitalist reforms of the university and to envisage a different future for the university. The book will appeal to activists, critical academics and those interested in the fate of higher education today. The eBook editions of this book are available open access under a CC-BY-NC-ND 3.0 licence on www.bloomsburycollections.com.